The Sorogan Method in Pesantren Education: Cognitive, Affective, and Psychomotor Learning Outcomes - M. Arif Khoiruddin; M. Ridlwan Nasir; Zakariyah (Indonesian Values and Character Education Journal, 2025)
The Sorogan method, as a traditional instructional model in pesantren, has rarely been examined systematically, particularly in relation to learning outcomes across cognitive, affective, and psychomotor domains. A key challenge is how this method can enhance academic competence, character development, and practical skills in a holistic manner. This study aims to analyze the contribution of the Sorogan method to the development of students’ academic abilities, character, and practical skills. The research employed a qualitative approach with a phenomenological design. Participants included active students, teachers (Mustahiq), and curriculum administrators. Data were collected through participatory observation, in-depth interviews, and document analysis. Data analysis was conducted through stages of reduction, thematic categorization, and interpretative synthesis following phenomenological procedures. The findings indicate that the Sorogan method enhances students’ cognitive abilities in understanding Arabic grammar structures, strengthens character formation through the internalization of discipline and ethical conduct, and hones psychomotor skills such as reading unvowelled texts, performing muroja’ah, and tashrif exercises. Intensive interaction with teachers facilitates holistic development and the internalization of moral values. The study concludes that the Sorogan method is both culturally relevant and pedagogically adaptive in supporting the development of students’ academic competence, character, and practical skills. The implications suggest that this method can serve as a reference for designing holistic instructional strategies that integrate individual mentoring, moral values, and hands-on practice in Islamic educational institutions.